Beltzville Lake, Lehigh River Basin, Pohopoco Creek, Pennsylvania, Condition Report. Dam Outlet Works and Spillway - ARMY ENGINEER DISTRICT PHILADELPHIA PA (1977)
The sixth periodic inspection of Beltzville Lake Dam was held on 11 and 12 Nov. 1976 by representatives of the North Atlantic Division and the Philadelphia District Army Corps of Engineers. The overall condition of the project is considered good. The two items of most concern to the inspection party were (1) the deterioration of the motor control units in the tower, and (2) the loss or faulty operations, since the dam's construction of a total of eight piezometers of the Warlam type, all of which are located downstream of the dam centerline (two of this total have been inoperative since October 1974). The motor control units have been replaced and action is in progress to correct other deficiencies prior to October 1977.